Total shrinkage and chloride ion penetration in concretes made with white Portland cement and blast furnace slag - Dellinghausen, Luciano Medeiros (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2009)
The aim of this study was to investigate the influence of the cement replacement content by slag as well the duration of curing on total shrinkage, chloride ion penetration and compressive strength of concretes made with high early-age strength cement and white Portland cement. Water-binder ratios of 0.30, 0.42 and 0.55, curing duration of 3 and 7 days, and cement replacement contents of 0%, 50% and 70% were investigated. In order to analyze the influence of the alkali activation on the properties investigated, a concrete made with 50% white Portland cement replacement content by slag and activated by sodium sulfate (4% of binder mass) was used. Before being immersed in the chloride  solution, the specimens were subjected to a drying period of 91 days. The results obtained revealed that an increase in the slag content decreased the compressive strength and the drying shrinkage values, as well as the depth of chloride penetration in both cements. Reducing the curing duration resulted in greater drying shrinkage and depth of chloride penetration for both cements, regardless of the slag content.